Developing teaching self-efficacy for aspiring academics. (1st January 2022) - Saetnan, Eli
Abstract : Self-efficacy theory provides a framework for understanding how confidence relates to teaching practice, and the role academic development might play in improving both confidence and academic practice either directly or indirectly. Here I use this framework to evaluate the outcomes of a programme developed to meet the needs of aspiring academics at a research-intensive university. Taking an interpretative phenomenological approach, I explored participants confidence journeys through semi-structured interviews to discover which experiences had the most impact on their teaching confidence. The findings are then used to discuss how elements of the academic development programme were particularly beneficial to building participants' confidence with implications for future programme design.